2023
DOI: 10.3390/ijms24087023
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Hyaluronan Nanofiber Membrane Immobilizing Aromatic Doxorubicin as Therapeutic and Regenerative Biomaterial

Abstract: Lesioned tissue requires synchronous control of disease and regeneration progression after surgery. It is necessary to develop therapeutic and regenerative scaffolds. Here, hyaluronic acid (HA) was esterified with benzyl groups to prepare hyaluronic acid derivative (HA-Bn) nanofibers via electrospinning. Electrospun membranes with average fiber diameters of 407.64 ± 124.8 nm (H400), 642.3 ± 228.76 nm (H600), and 841.09 ± 236.86 nm (H800) were obtained by adjusting the spinning parameters. These fibrous membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In the following, some examples of electrospun grafted HA will be discussed (Table 3). wound-dressing for chronic diabetic wounds [38] benzyl bromide HA-benzyl ester/ Doxorubicin Doxorubicin encapsulation anti-melanoma drug delivery system [39] C 8 /C 12 /C 18 Alkyl Amine + EDA alkylated-HA/ PVA/HPβCD/dexamethasone EDC/NHS crosslinking scaffold for periodontal regeneration [40] Temporin Ra HA/Chitosan/PVA Peptide Loading Antimicrobial wound healing dressing [52] REDV peptide (P1) PCL Layer-by-layer deposition of PDDA [a] , SePEI [b] RGD-TCO [c] (P4) PCL-Tz [d] LbL deposition of HA-TCO and HA-Tz + final P4-TCO deposition therapeutic implants for the treatment of vocal fold scarring [80] Ac-KGGPQVTRGDVFTMP (P5) PVA/HA P5 conjugation with EDC/NHS on glutaraldehyde crosslinked nanofibers Scaffold for iPSCs growth and proliferation [81] [a]…”
Section: Electrospun Scaffolds Based On Hyaluronic Acid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, some examples of electrospun grafted HA will be discussed (Table 3). wound-dressing for chronic diabetic wounds [38] benzyl bromide HA-benzyl ester/ Doxorubicin Doxorubicin encapsulation anti-melanoma drug delivery system [39] C 8 /C 12 /C 18 Alkyl Amine + EDA alkylated-HA/ PVA/HPβCD/dexamethasone EDC/NHS crosslinking scaffold for periodontal regeneration [40] Temporin Ra HA/Chitosan/PVA Peptide Loading Antimicrobial wound healing dressing [52] REDV peptide (P1) PCL Layer-by-layer deposition of PDDA [a] , SePEI [b] RGD-TCO [c] (P4) PCL-Tz [d] LbL deposition of HA-TCO and HA-Tz + final P4-TCO deposition therapeutic implants for the treatment of vocal fold scarring [80] Ac-KGGPQVTRGDVFTMP (P5) PVA/HA P5 conjugation with EDC/NHS on glutaraldehyde crosslinked nanofibers Scaffold for iPSCs growth and proliferation [81] [a]…”
Section: Electrospun Scaffolds Based On Hyaluronic Acid Derivativesmentioning
confidence: 99%
“…In vitro cell experiments demonstrated that HA-DOX nanofiber had a considerable inhibitory effect on murine melanoma cell-lines. [39] The introduction of alkylamine pendant moieties at different lengths (C x ) to HA (HA-EDA-C x ) was carried out by Federico et al and the osteoinductive potential of HA-based electrospun scaffolds was evaluated). [40] HA derivatives were blended with PVA and 2-hydroxypropylcyclodextrin to improve electrospinning process.…”
Section: Small Molecule Decorated Ha Derivativesmentioning
confidence: 99%
“…Natural polymers suitable for the preparation of nanofibers mainly fall into two categories: polysaccharides and proteins. Polysaccharides include chitosan [ 60 ], starch [ 61 ], alginates [ 62 ], hyaluronic acid [ 63 ], and cellulose [ 64 ]; while protein-based polymers include collagen [ 65 ], gelatin [ 66 ], fibrinogen [ 67 ], silk proteins [ 68 ], sericin [ 69 ], elastin [ 70 ], keratin [ 71 ], and plant proteins [ 72 ]. Table 1 lists the polymers that can be used to prepare nanofibrous scaffolds.…”
Section: Nanofiber Scaffold Technologymentioning
confidence: 99%
“…Blended electrospinning allows for the fabrication of drug-loaded nanofiber scaffolds by combining drugs with scaffold materials and then utilizing electrospinning technology [ 63 ]. This approach allows for excellent biocompatibility and mechanical properties, making them suitable for various biomedical applications [ 199 ].…”
Section: Nanofiber Scaffold Technologymentioning
confidence: 99%